The Effect of Celebrity Endorser and Content Marketing on Purchase Intention of Fashion Muslim - Fauziyah Putri; Achsania Hendratmi (Jurnal Ekonomi Syariah Teori dan Terapan, 2022)
ABSTRAK Halal fashion saat ini menjadi salah satu sektor yang diminati konsumen di Indonesia. Mayoritas penduduk Indonesia yang merupakan muslim menjadikan pangsa pasar industri fashion Muslim sangat besar. Permintaan produk fashion muslim semakin tinggi karena kesadaran perempuan Muslim dalam menutup aurat juga sudah tinggi. Apalagi, konsumen saat ini suka melihat fashion influencer di sosial media seperti Instagram. Serta penggunakan content marketing yang menarik juga mempengaruhi konsumen untuk membeli sebuah produk. Penjualan produk fashion muslim semakin mudah diakses konsumen dengan andanya media digital untuk melihat dan bertransaksi. Tujuan penelitian ini adalah untuk melihat pengaruh pendukung selebriti dan pemasaran konten. Penelitian ini menggunakan metode kuantitatif. Dengan teknik data yaitu kuisioner yang disebarkan secara online kepada 100 responden perempuan muslim yang pernah mengakses platform online brand fashion muslim Vanilla Hijab. Teknik analisis yang digunakan dalam penelitian ini yaitu regresi linier berganda. Hasil dari penelitian ini menunjukkan celebrity endorser memiliki pengaruh positif signifikan terhadap niat beli, dan konten pemasaran juga memiliki pengaruh positif signifikan terhadap niat beli toko online fashion Vanilla Hijab. Kata-Kunci: Celebrity Endorser, Content Marketing, Purchase Intention, Fashion Muslim.   ABSTRACT Halal fashion is currently one of the sectors that consumers in Indonesia are interested in. The majority of Indonesia's population who are Muslim makes the market share of the Muslim fashion industry very large. The demand for Muslim fashion products is getting higher because the awareness of Muslim women in covering their genitals is high. Moreover, consumers today like to see fashion influencers on social media like Instagram. And the use of attractive content marketing also influences consumers to buy a product. The sale of Muslim fashion products is increasingly accessible to consumers by relying on digital media to view and transact. The purpose of this study was to examine the influence of celebrity supporters and content marketing. This research uses quantitative methods. With the data technique, namely a questionnaire distributed online to 100 Muslim female respondents who have accessed the online platform for the Muslim fashion brand Vanilla Hijab. The analysis technique used in this study is multiple linear regression. The results of this study indicate celebrity endorsers have a significant positive effect on purchase intention, and marketing content also has a significant positive effect on purchase intention of Vanilla Hijab fashion online shop. Keywords: Celebrity Endorser, Content Marketing, Purchase Intention, Fashion Muslim.   DAFTAR PUSTAKA Abbas, A., Afshan, G., & Khan, S. B. (2018). The effect of celebrity endorsement on customer purchase intention: A comparative study predictors and consequences of human resource outsourcing view project internal marketing view project. Current Economics and Management Research, 4(1), 1–10. Abdurrahim, A., & Sangen, M. (2019). Pengaruh content marketing, sales promotion, personal selling, dan advertising terhadap minat beli konsumen pada hotel biuti di Banjarmasin. Jurnal Sains Manajemen Dan Kewirausahaan, 3(1), 42–47. http://ppjp.ulm.ac.id/journal/index.php/jsmk Andreas, R. (2013). The big book of content marketing: Use Strategies and SEO Tactics to Build Return-Oriented KPIs for Your Brand's Content. Andreas.com. Audia, D. S., Jayawinangun, R., & Ferdinan, F. (2018). Pengaruh celebrity endorser terhadap minat pembelian produk Aidi.Id (Studi pada followers instagram Aidi.Id). Jurnal Penelitian Sosial Ilmu Komunikasi, 3(1), 76–95. https://doi.org/10.33751/jpsik.v3i1.1012 Badan Pusat Statistik. (2016). No Title. https://se2016.bps.go.id/umkumb/ Bappenas. (2019). Ekonomi Syariah Indonesia 2019-2024. Jakarta: Bappenas. Belch, G. E., & Belch, M. A. (2009). Advertising and promotion: An integrated marketing communications perspective. New York: McGraw-Hill Education. Calesta, K. (2018, October 24). Daftar online shop hijab & modest wear terbaik 2018. Retrieved from https://www.cosmopolitan.co.id/article/read/10/2018/14864/daftar-online-shop-hijab-modest-wear-terbaik-2018 Chetioui, Y., Benlafqih, H., & Lebdaoui, H. (2020). How fashion influencers contribute to consumers’ purchase intention. Journal of Fashion Marketing and Management, 24(3), 361–380. https://doi.org/10.1108/JFMM-08-2019-0157 Delener, N. (1994). Religious contrasts in consumer decision behaviour patterns: Their dimensions and marketing implications. European Journal of Marketing, 28(5), 36–53. https://doi.org/10.1108/03090569410062023 Duranto, D., & Liana, C. (2004). Analisis efektivitas iklan televisi softener soft & fresh di Jakarta dan sekitarnya dengan menggunakan consumen decision model. Jurnal Ekonomi Perusahaan, 11(1), 35–55. Ferdinand, A. (2002). Structural equation modelling dalam penelitian manajemen. Semarang: Badan Penerbit Universitas Diponegoro. Gao, D. (2018). Research on the influencing factors of customer’s purchase intention in the context of content marketing. Proceedings of the 2018 2nd International Conference on Education Science and Economic Management (ICESEM 2018), 1184–1189. https://doi.org/10.2991/icesem-18.2018.277 Joe, P. (2009). What Is Content Marketing?. Retrieved from https://contentmarketinginstitute.com/ what-is-content-marketing/ Kim, J., Kang, S., & Lee, K. H. (2020). How social capital impacts the purchase intention of sustainable fashion products. Journal of Business Research, 117(November 2017), 596–603. https://doi.org/10.1016/j.jbusres.2018.10.010 Lapod, A. C. (2020, October 28). Belajar dari CEO Vanilla Hijab, cara mulai bisnis fashion dengan modal kecil. Retrieved from https://kumparan.com/kumparanwoman/belajar-dari-ceo-vanilla-hijab-cara-mulai-bisnis-fashion-dengan-modal-kecil-1uTjF96VapG/full Lee, J., & Lee, J. N. (2015). How purchase intention consummates purchase behaviour: The stochastic nature of product valuation in electronic commerce. Behaviour and Information Technology, 34(1), 57–68. https://doi.org/10.1080/0144929X.2013.853837 Lu, L. C., Chang, W. P., & Chang, H. H. (2014). Consumer attitudes toward blogger’s sponsored recommendations and purchase intention: The effect of sponsorship type, product type, and brand awareness. Computers in Human Behavior, 34, 258–266. https://doi.org/10.1016/j.chb.2014.02.007 Phua, J., Lin, J. S. (Elaine), & Lim, D. J. (2018). Understanding consumer engagement with celebrity-endorsed E-Cigarette advertising on instagram. Computers in Human Behavior, 84(March), 93–102. https://doi.org/10.1016/j.chb.2018.02.031 Pusat Pengkajian dan pengembangan Ekonomi Islam. (2008). Ekonomi Islam. Jakarta: PT Raja Grafindo Persada. Rocha, P. I., Caldeira de Oliveira, J. H., & Giraldi, J. d. M. E. (2019). Marketing communications via celebrity endorsement: an integrative review. Benchmarking, 27(7), 2233–2259. https://doi.org/10.1108/BIJ-05-2018-0133 Royan, F. M. (2004). Marketing selebrities (Selebriti dalam iklan dan strategi selebriti memasarkan diri sendiri). Jakarta: PT Elex Media Komputindo. Schaefer, M. (2016). Learn to create effective content by putting it through the RITE test. Retrieved from https://businessesgrow.com/2016/12/08/create-effective-content/ Seock, Y. K., & Norton, M. (2007). Attitude toward internet web sites, online information search, and channel choices for purchasing. Journal of Fashion Marketing and Management, 11(4), 571–586. https://doi.org/10.1108/13612020710824616 Seyyedamiri, N., & Tajrobehkar, L. (2019). Social content marketing, social media and product development process effectiveness in high-tech companies. International Journal of Emerging Markets, 16(1), 75–91. https://doi.org/10.1108/IJOEM-06-2018-0323 Shafie, S., & Othman, M. N. (2008). Halal Certification: An international marketing issues and challenges. Shimp, T. (2003). Periklanan promosi dan aspek tamnahan komunikasi pemasaran terpadu. Jakarta: Erlangga. Sokolova, K., & Kefi, H. (2020). Instagram and youtube bloggers promote it, why should I buy? How credibility and parasocial interaction influence purchase intentions. Journal of Retailing and Consumer Services, 53(January). https://doi.org/10.1016/j.jretconser.2019.01.011 Sugiyono. (2017). Metode penelitian kuantitatif, kualitatif, dan R&D. Bandung: CV. Alfabeta. Wang, J. S., Cheng, Y. F., & Chu, Y. L. (2012). Effect of celebrity endorsements on consumer purchase intentions: Advertising effect and advertising appeal as mediators. Human Factors and Ergonomics in Manufacturing & Service Industries, 23(5), 357-367. https://doi.org/10.1002/hfm.20336 Ward, J. (2016). A content analysis of celebrity instagram posts and parasocial interaction. Elon Journal of Undergraduate Research in Communications, 7(1). Wijaya, P. S. M., & Teguh, C. (2012). Faktor-faktor yang mempengaruhi minat beli di online shop Specialis Guess. Jurnal Riset Manajemen dan Bisnis, 7(2), 147–160. http://dx.doi.org/10.21460/jrmb.2012.72.79 Xiang, L., Zheng, X., Lee, M. K. O., & Zhao, D. (2016). Exploring consumers’ impulse buying behavior on social commerce platform: The role of parasocial interaction. International Journal of Information Management, 36(3), 333–347. https://doi.org/10.1016/j.ijinfomgt.2015.11.002 Yodi H. P., Widyastuti, S., & Noor, L. S. (2020). The effects of content and influencer marketing on purchasing decisions of fashion Erigo company. 1(2), 345–257. https://doi.org/10.38035/dijefa.v1i2.309